2017
DOI: 10.1111/imj.13502
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate guidelines for treatment and prevention of myeloma bone disease

Abstract: Multiple myeloma (MM) is a haematological malignancy characterised by the clonal proliferation of plasma cells in the bone marrow. More than 80% of patients with MM display evidence of myeloma bone disease (MBD), characterised by the formation of osteolytic lesions throughout the axial and appendicular skeleton. MBD significantly increases the risk of skeletal-related events such as pathologic fracture, spinal cord compression and hypercalcaemia. MBD is the result of MM plasma cells-mediated activation of oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 108 publications
(226 reference statements)
1
19
0
Order By: Relevance
“…In advanced NSCLC with bone metastases, adding Zol to chemotherapy improves OS as compared with chemotherapy alone (578 days versus 384 days, p<0.0001) [141]. In castration-resistant prostate cancer, Zol reduces skeletal-related events, especially when combined with docetaxel [143]. In addition, Zol has been shown to reduce skeletal-related events in multiple myeloma patients [143].…”
Section: Bisphosohonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced NSCLC with bone metastases, adding Zol to chemotherapy improves OS as compared with chemotherapy alone (578 days versus 384 days, p<0.0001) [141]. In castration-resistant prostate cancer, Zol reduces skeletal-related events, especially when combined with docetaxel [143]. In addition, Zol has been shown to reduce skeletal-related events in multiple myeloma patients [143].…”
Section: Bisphosohonatesmentioning
confidence: 99%
“…In castration-resistant prostate cancer, Zol reduces skeletal-related events, especially when combined with docetaxel [143]. In addition, Zol has been shown to reduce skeletal-related events in multiple myeloma patients [143].…”
Section: Bisphosohonatesmentioning
confidence: 99%
“…In cancer patients, several studies demonstrated a longer duration and higher doses of IV BP as important risk factors for ONJ (Bamias et al, ; Fehm et al, ; Hoff et al, ; Ortega et al, ), and a study reported reduced incidence of ONJ following BP dose reductions along with active dental intervention (Sim, Sanders, Borromeo, Seymour, & Ebeling, ). In 2017, Australian guidelines on BP treatment in myeloma recommended ceasing BP in patients with a low risk of skeletal‐related events, after 1–2 years of BP treatment (Lee et al, ). In a position paper in 2009, the American Association of oral and maxillofacial surgeons (AAOMS) recommended at least a 3‐month drug holiday before oral surgery (Ruggiero et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 In all countries in which bisphosphonates are available, they are recommended for all patients receiving myeloma therapy for symptomatic disease regardless of documented bone disease, although optimal duration and effectiveness in the relapsed or refractory setting are not fully elucidated. [3][4][5] Considering that the patients in the ENDEAVOR trial were recruited from 198 hospital or outpatient oncology centres in 27 countries in Europe, North America, South America, and the Asia-Pacific region, great differences in bisphosphonate administration methods probably existed. Thus, because bisphosphonates could be a potential confounding factor for overall survival, we suggest that the authors provide the detailed information about the balance between groups in terms of bisphosphonate use, including types, dosing schedules, and durations.…”
mentioning
confidence: 99%